2015
DOI: 10.1007/s12011-015-0392-6
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Reverses Lipid Peroxidation but not Acetylcholinesterase Activity Induced by Long-Term Exposure to Low Aluminum Levels in Rat Brain Regions

Abstract: Aluminum (Al) is the most widely distributed metal in the environment and is extensively used in daily life leading to easy exposure to human beings. Besides not having a recognized physiological role, Al may produce adverse effects through the interaction with the cholinergic system contributing to oxidative stress. The present study evaluated, in similar conditions of parenteral nutrition, whether the reaction of silicon (SiO2) with Al(3+) to form hydroxyaluminosilicates (HAS) reduces its bioavailability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…However, AChE activity is increased within and around the Aβ plaques. Noremberg et al [18] showed the contrary, that is, a decrease of the AChE activity in the presence of aluminum in the hippocampus and cortex, which would be a precursor of Alzheimer’s disease. It is important to emphasize that since cerebral AChE is an important regulator of behavioral process, the decreased AChE activity found in the cortex and hippocampus may be an indicator of aluminum-induced damage in the brain.…”
Section: Aluminum As An Alzheimer’s Disease Risk Factormentioning
confidence: 99%
See 2 more Smart Citations
“…However, AChE activity is increased within and around the Aβ plaques. Noremberg et al [18] showed the contrary, that is, a decrease of the AChE activity in the presence of aluminum in the hippocampus and cortex, which would be a precursor of Alzheimer’s disease. It is important to emphasize that since cerebral AChE is an important regulator of behavioral process, the decreased AChE activity found in the cortex and hippocampus may be an indicator of aluminum-induced damage in the brain.…”
Section: Aluminum As An Alzheimer’s Disease Risk Factormentioning
confidence: 99%
“…In line with the González-Muñoz et al [43] study, aluminum nitrate intoxication impairs the brain antioxidant status. Noremberg et al [18], based on many investigations, suggested that the brain may be particularly vulnerable to oxidative damage due the relationship between aluminum accumulation and oxidative damage in the brain [171]. As previously commented on, although aluminum is not a transition metal and therefore cannot initiate peroxidation, aluminum induces alteration in brain metal homeostasis [17], mainly affecting minerals with antioxidant properties [40].…”
Section: Effect Of Non-alcoholic Beer Silicon and Hops On Brain mentioning
confidence: 99%
See 1 more Smart Citation
“…Al causes changes in acetylcholinesterase activity from acute and subacute exposure as well as significant deterioration in cognitive functions in rats (21,66,78,108,166). Observation of the central cholinergic system after Al exposure, of 10 mg/kg of body weight/ day for 4 weeks, revealed a deleterious effect on the activities of biosynthetic (choline acetyltransferase) and hydrolytic (acetylcholinesterase) enzymes of the neurotransmitter acetylcholine.…”
Section: Al Induced Symptoms Mimic Ad Symptomsmentioning
confidence: 99%
“…Aluminium exerts its adverse effects in different organs, including the nervous (Bondy, 2016;Noremberg et al, 2015), skeletal muscle (Aghilinejad, Mousavi, Nouri, & Ahmadi, 2012), respiratory (Shaaban, Zayet, Aboufaddan, & Elghazally, 2016), cardiovascular (Schmidt et al, 2016) and urogenital system (Berihu, 2015;Farajbakhsh, Amjadi, Manzoori, Ardalan, & Jouyban, 2016;Sombra et al, 2003).…”
mentioning
confidence: 99%